EKSPRESI KECEMASAN NETIZEN DI MEDIA SOSIAL FACEBOOK TENTANG PANDEMI COVID-19 (Netizens' Expressions of Anxiety on Facebook Social Media Regarding the Covid-19 Pandemic) - Sultan Sultan; Muhammad Rapi; Muhammad Bahly Basri (Balai Bahasa Sulawesi Selatan, 2022)
Discourse studies and the Covid-19 pandemic have attracted the attention of previous researchers with various topics. However, studies that focus on the anxiety of netizens as expressed through social media Facebook have not been carried out. Therefore, this research is designed to fill the gap in the literature by revealing the forms and linguistic features utilized in representing the anxiety of netizens through the social media Facebook. Qualitative research using a critical discourse analysis approach was conducted on uploads by netizens on Facebook which were published between March and May 2020 and were selected purposively. The collected data is processed by thematic analysis. The results of the study show that netizens' anxiety about the Covid-19 pandemic is manifested in religious expressions, personal reflections, fears and worries, hopes, anger, and advice. The various forms of expression found represent messages of anxiety and efforts to build public awareness to comply with health protocols. The linguistic features used include collective and exclusive pronouns, repetition, metaphor, parallelism, and pragmatic markers of invitations and orders. This linguistic feature functions to foster collectivity, convey feelings, confirm information, and encourage public participation. The research findings provide a new perspective on the study of disaster discourse and expand the area of language studies in a pandemic situation.Keywords: Covid-19, language expression, anxiety, discourse studies, disaster discourseKajian wacana dan pandemi Covid-19 telah menarik perhatian para peneliti terdahulu dengan beragam topik. Namun demikian, studi yang berfokus pada kecemasan netizen yang diekspresikan melalui media sosial facebook belum dilakukan. Oleh karena itu, penelitian ini didesain untuk mengisi kesenjangan literatur dengan mengungkap bentuk dan fitur linguistik yang didayagunakan dalam merepresentasikan kecemasan netizen melalui media sosial facebook. Penelitian kualitatif dengan ancangan analisis wacana kritis dilakukan terhadap unggahan netizen di facebook yang terbit antara Maret sampai Mei 2020 dan dipilih secara purposive. Data terkumpul diolah dengan analisis tematik. Hasil penelitian menunjukkan bahwa kecemasan netizen terhadap pandemi Covid-19 diwujudkan dalam ekspresi religi, refleksi pribadi, ketakutan dan kekhawatiran, harapan, kemarahan, dan nasihat. Beragam bentuk ekspresi yang ditemukan merepresentasikan pesan kegelisahan dan upaya membangun kesadaran publik untuk menaati protokol kesehatan. Fitur linguistik yang didayagunakan mencakup pronomina kolektif dan eksklusif, repetisi, metafora, paralelisme, dan pemarkah pragmatic ajakan dan perintah. Fitur linguistic itu berfungsi menumbuhkan kolektivitas, menyampaikan perasaan, menegaskan informasi, dan mendorong partisipasi publik. Temuan penelitian memberikan perspektif baru terhadap studi wacana bencana dan memperluas area kajian bahasa dalam situasi pandemi.Kata kunci: Covid-19, ekspresi berbahasa, kecemasan, studi wacana, wacana bencana